Effects of 9-cis-retinoic acid on the proliferation and apoptosis of cutaneous T-cell lymphoma cells. Issue 1 (January 2019) - Yang, Hua; Tao, Yue; Zhang, Mengli; Ma, Pengcheng; Li, Lingjun; Diao, Qingchun
Abstract : The vitamin A derivative 9-cis-retinoic acid (9-cis-RA) has been used for the treatment and prevention of cutaneous T-cell lymphoma (CTCL). However, the precise mechanism by which 9-cis-RA treatment ameliorates CTCL remains elusive. Our research shows that 9-cis-RA inhibits proliferation and induces apoptosis in CTCL cells in a dose-dependent and time-dependent manner. 9-Cis-RA also induced G0/G1 cell cycle arrest by downregulation of cyclin D1 . We confirmed that 9-cis-RA significantly decreased phosphorylation of JAK1, STAT3, and STAT5 and downregulated Bcl-xL and cyclin D1, indicating that 9-cis-RA inhibited the activation of JAK/STAT signaling. Meanwhile, 9-cis-RA also activated classical RA-mediated transcription by retinoic acid receptors ( RAR ) and/or retinoid X receptors ( RXR ) in a CTCL cell line. Thus, 9-cis-RA may be effective for chemotherapy and may prevent human CTCL by inhibiting proliferation and inducing apoptosis by inhibition of the JAK/STAT pathway and activation of the RAR/RXR pathway.